Histologic pulmonary lesions of SARS-CoV-2 in 4 nonhuman primate species: An institutional comparative review. Issue 4 (July 2022) - Clancy, Chad S.; Shaia, Carl; Munster, Vincent; de Wit, Emmie; Hawman, David; Okumura, Atsushi; Feldmann, Heinz; Saturday, Greg; Scott, Dana
Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an emergent, amphixenotic infection that resulted in a pandemic declaration in March 2020. A rapid search for appropriate animal models of this newly emergent viral respiratory disease focused initially on traditional nonhuman primate research species. Nonhuman primate models have previously been shown to be valuable in evaluation of emerging respiratory coronaviruses with pandemic potential (ie, SARS-CoV and Middle East respiratory syndrome coronavirus). In this article, we review the pulmonary histopathologic characteristics and immunohistochemical evaluation of experimental SARS-CoV-2 infection in the rhesus macaque, pigtail macaque, African green monkey, and squirrel monkey. Our results indicate that all evaluated nonhuman primate species developed variably severe histopathologic changes typical of coronavirus respiratory disease characterized by interstitial pneumonia with or without syncytial cell formation, alveolar fibrin, and pulmonary edema that progressed to type II pneumocyte hyperplasia. Lesion distribution was multifocal, frequently subpleural, and often more severe in lower lung lobes. However, squirrel monkeys showed the least severe and least consistent lesions of the evaluated nonhuman primates. Additionally, our results highlight the disparate physical relationship between viral antigen and foci of pulmonary lesions. While classic respiratory coronaviral lesions were observed in the lungs of all nonhuman primates evaluated, none of the primates exhibited severe lesions or evidence of diffuse alveolar damage and therefore are unlikely to represent the severe form of SARS-CoV-2 infection observed in fatal human cases.